Novel Solid Dispersions of Naphthoquinone Using Different Polymers for Improvement of Antichagasic Activity - Verônica da Silva Oliveira; Elen Diana Dantas; Anna Thereza de Sousa Queiroz; Johny Wysllas de Freitas Oliveira; Marcelo de Sousa da Silva; Patricia Garcia Ferreira; Fernando de Carvalho da Siva; Vitor Francisco Ferreira; Ádley Antonini Neves de Lima (MDPI AG, 2020)
IVS320 (3a,10b-dihydro-1H-cyclopenta[b]naphtho[2,3-d]furan-5,10-dione) is a naphthoquinone that has low solubility in aqueous medium, a physical behavior that limits its biological activities, considering that compounds from this class have several activities. In this work, solid dispersions (SDs) prepared between IVS320 and polymers hydroxypropyl methylcellulose (HPMC), polyethylene glycol (PEG), and polyvinylpyrrolidone (PVP) were developed using physical mixture (PM), kneading (KN), and rotary evaporation (RE) methods. Dispersions were investigated using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetry (TG), powder X-ray diffraction (PXRD), and scanning electron microscopy (SEM). In addition, in vitro antiparasitic activity in Trypanosoma cruzi Y strains was evaluated. Physical-chemical characterization demonstrated the formation of SDs through the interaction of IVS320 with polymeric matrices. SDs of IVS320-polymer presented a significant potentiation of antichagasic activity, with inhibitory growth around 62% (IVS320-HPMC/RE), 55% (IVS320-PEG/RE), and 85% (IVS320-PVP/RE), while pure IVS320 showed a value of 48% for the highest concentrations evaluated (50 µg/mL).